Protocol analysis : verbal reports as data - Ericsson, Anders, 1947-2020; Simon, Herbert A. (Herbert Alexander), 1916-2001 (MIT Press, 1993)
Verbal data is used to study cognitive processes in many areas of psychology. Here, the authors review major advances in verbal reports over the past decade, including new evidence on how giving verbal reports affects subjects' cognitive processes, and on the validity of such reports.